RESILIENSI PROGRAM POSBINDU PTM PADA MASA PANDEMI COVID-19: TANTANGAN DAN ADAPTASI DI PUSKESMAS KOTA YOGYAKARTA - Munana, Nila; Mahendradhata, Yodi; Prawidya Putri, Likke (Journal of Health Service Management, 2025)
Non-Communicable Diseases (NCDs) are a major cause of death in Indonesia, leading the government to implement the Integrated Health Post (Posbindu PTM) program for early detection and risk factor control. The COVID-19 pandemic significantly impacted the implementation of Posbindu, resulting in a decline in service coverage in several areas. This study aims to explore the barriers and enablers to resilient Posbindu-PTM (community-based NCD screening program) at Yogyakarta City, Indonesia. We conducted a qualitative study by reviewing regulations and interviewing 10 informants by using purposively-selected Community, Community Health Workers (CHWs) and health professionals in two public community health centers (puskesmas) about Posbindu-PTM program. The collected information was analyzed using content analysis. The results show The pandemic led to a decrease in NCD screening coverage from 100% (2019) to 58.73% (2021) at Gondokusuman I, while at Umbulharjo II, it declined to 88%. Key factors contributing to resilience included community involvement, flexible policy support, and service adaptation with strict health protocols. We conclude that, the enable improving resilience of Posbindu-PTM, the role of the community, leadership from DHA and puskesmas staff is imperative. It is also critical to ensure adequate human resources for health, including health professional and CHWs, not only to perform routine activities in NCD screening, but also for managing information systems